2006
DOI: 10.1038/sj.onc.1209346
|View full text |Cite
|
Sign up to set email alerts
|

A crosstalk between the Wnt and the adhesion-dependent signaling pathways governs the chemosensitivity of acute myeloid leukemia

Abstract: Relapses following chemotherapy are a major hindrance to patients' survival in acute myeloid leukemia (AML). To investigate the role of the hematopoietic niche in the chemoresistance of leukemic cells, we examined two pathways: one mediated by adhesion molecules/integrins, and the other by soluble factors of the morphogen Wnt pathway. In our study, both the adhesion of leukemic blasts to fibronectin and the addition of Wnt antagonists induced, independently, resistance of AML cells to daunorubicin in a cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 39 publications
11
108
0
Order By: Relevance
“…Moreover, we show that inhibition of GSK-3 sensitised kidney cancer cells to Docetaxel suggesting that GSK-3 might contribute to renal cancer chemoresistance. Our findings are supported by another study showing that GSK-3b positively regulates NF-kBmediated chemoresistance in acute myeloid leukaemia (De Toni et al, 2006). Recently, it has been shown that GSK-3b inhibition enhanced Sorafenib-induced apoptosis in melanoma cells (Panka et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, we show that inhibition of GSK-3 sensitised kidney cancer cells to Docetaxel suggesting that GSK-3 might contribute to renal cancer chemoresistance. Our findings are supported by another study showing that GSK-3b positively regulates NF-kBmediated chemoresistance in acute myeloid leukaemia (De Toni et al, 2006). Recently, it has been shown that GSK-3b inhibition enhanced Sorafenib-induced apoptosis in melanoma cells (Panka et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, Wnt5a appears to inhibit proliferation of hematopoietic cells and might function as a tumor suppressor in hematopoietic tissue. The hypothesis that Wnt signals not only contribute to proliferation and self-renewal in AML but partially also function as tumor suppressors is further supported by a study of de Toni et al 141 This group was able to show that addition of different antagonists of the canonical Wnt/ b-catenin pathway, such as sFRP-1, Dkk-1 and Wnt5a to AML blasts or U937 cells induced resistance to daunorubicin, whereas incubation with the Wnt agonist Wnt3a increased chemosensitivity. Drug resistance mediated by sFRP-1 required GSK3b and nuclear factor-kB (NF-kB) suggesting a crosslink between Wnt signaling and NF-kB activation in AML.…”
Section: Other Mechanisms Of Aberrant Wnt Signaling In Amlsupporting
confidence: 55%
“…Drug resistance mediated by sFRP-1 required GSK3b and nuclear factor-kB (NF-kB) suggesting a crosslink between Wnt signaling and NF-kB activation in AML. 141 Osteoblasts that play a key role in the maintenance of the hematopoietic niche were shown to support drug resistance of U937 cells adhering onto osteoblasts by triggering sFRP-1 secretion. 141 As a consequence Wnt proteins seem not only to support selfrenewal and proliferation of AML cells but can also partially act as tumor suppressors and chemosensitizers.…”
Section: Other Mechanisms Of Aberrant Wnt Signaling In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…GSK-3b activity seems also important for adhesion and Wnt-pathway b-catenin expression and drug resistance in AML cells. 142,143 b-Catenin expression in AML cells predicts enhanced clonogenic capacities and is associated with a poor prognosis. 143 Thus, GSK-3b also plays key roles in regulating proliferative loops involved in malignant transformation of hematopoietic cells.…”
Section: Interactions Of Akt With Activator Proteinsmentioning
confidence: 99%